Disharmonization in Managing Government Affairs in Batam City, Riau Islands Province - Anton Permana; Djohermansyah Djohan; Ika Sartika; Sampara Lukman (International Journal Labs, 2022)
This study aims to find out and explain how the dualism of government affairs management occurs in Batam City, Riau Islands Province and the efforts of the Central Government in overcoming this dualism of authority, as well as formulating an ideal model for managing government affairs in Batam City, Riau Islands Province. This study used a qualitative approach with a descriptive type and in the form of field research (field research). Using management theories in government as well as several other supporting theories in explaining the picture of dualism and overlaps that occur in the management of government affairs in Batam City. The fact that the main problem in government management in Batam City is the occurrence of disputes in terms of authority between the City Government and the Batam Concession Agency such as HPL (Land Management Rights), taxation, licensing, management of state vital assets, tourism and staffing; The efforts of the Central Government in dealing with this problem is to issue Government Regulation Number 62 of 2019 which states that the Mayor of Batam becomes the ex-officio Head of BP Batam with the aim of eliminating disputes over authority that have occurred, but in its journey there are still authorities which are in principle the same but still carried out and issued by the Batam City Government and the Batam Concession Agency. The model produced in this study is the TDM Special Autonomy model, namely Totality, Decentralization, and Monetization as a frame of reference in implementing special autonomy.